2021
DOI: 10.1016/j.bbih.2021.100346
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the gut microbiota among Veterans with unique military-related exposures and high prevalence of chronic health conditions: A United States-Veteran Microbiome Project (US-VMP) study

Abstract: The gut microbiome is impacted by environmental exposures and has been implicated in many physical and mental health conditions, including anxiety disorders, affective disorders, and trauma- and stressor-related disorders such as posttraumatic stress disorder (PTSD). United States (US) military Veterans are a unique population in that their military-related exposures can have consequences for both physical and mental health, but the gut microbiome of this population has been understudied. In this publication, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 90 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…Anxiety disorders represent the most prevalent category of mental illnesses, encompassing conditions such as generalized anxiety disorder (GAD), separation anxiety, selective mutism, specific phobias, social anxiety disorder (SAD), panic disorder, and agoraphobia ( Penninx et al, 2021 ). The link between dysbacteriosis (microbial imbalances) and anxiety disorders, spanning the spectrum of anxiety conditions ( Stanislawski et al, 2021 ) including specific subtypes like GAD ( Chen et al, 2019 ) and SAD ( Butler et al, 2023 ), has been extensively studied. Additionally, preclinical research has delved into the influence of gut microbiota on behaviors related to anxiety ( Neufeld et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders represent the most prevalent category of mental illnesses, encompassing conditions such as generalized anxiety disorder (GAD), separation anxiety, selective mutism, specific phobias, social anxiety disorder (SAD), panic disorder, and agoraphobia ( Penninx et al, 2021 ). The link between dysbacteriosis (microbial imbalances) and anxiety disorders, spanning the spectrum of anxiety conditions ( Stanislawski et al, 2021 ) including specific subtypes like GAD ( Chen et al, 2019 ) and SAD ( Butler et al, 2023 ), has been extensively studied. Additionally, preclinical research has delved into the influence of gut microbiota on behaviors related to anxiety ( Neufeld et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The session closed with a discussion of discerning alterations in gut, oral, and skin microbiomes associated with chronic physical and psychological health conditions and medication use, as part of the United States-Veteran Microbiome Project [10][11][12]. The goal is to better understand the relationship between human microbiota, health conditions in veterans, and effectiveness of medications.…”
Section: Human Microbiome: Stress Responsementioning
confidence: 99%
“…Veteran Microbiome Project has begun research into the skin, gut, and oral microbiome of an unstably housed population. Initial results showed that the frequency of homelessness was associated with gut microbial composition ( 9 ), thereby prompting future work focused on potential relationships between unstable housing, the microbiome, and physical and mental health.…”
Section: Sociocultural Interactionsmentioning
confidence: 99%